Quality and shelf life of blueberry (Vaccinium myrtillus) with edible mucilage coating of coffee (Coffea arabica) - Marín, Mercedes (2024)
Blueberries are highly valued globally for their high antioxidant content and resilience to diverse agroclimatic conditions. This study examines the effects of coating blueberries (Vaccinium myrtillus) with an edible coating (CR) made from coffee mucilage on their shelf life and quality. The coating was applied at three different concentrations of coffee mucilage (3%, 5%, and 7%) and subjected to three storage temperatures (20±2 ºC, 4 ºC, and -1 ºC). The research findings indicate that the utilization of a coating formulation containing 5% coffee mucilage, 2.5% starch, and 20% glycerol effectively reduces weight loss in berries at three storage temperatures (20±2, 4, -1 ºC), diminishes titratable acidity, and preserves sugars in comparison to uncoated berries. This creates the possibility of using the coffee-mucilage-based coating as a viable replacement to prolong the shelf life of blueberry and Andean berry crops.